2022
DOI: 10.1136/bmjopen-2022-062703
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a systematic review and meta-analysis of minimal important differences for generic multiattribute utility instruments

Abstract: IntroductionGeneric multiattribute utility instruments (MAUIs) are efficient tools for determining and enumerating health-related quality of life. MAUIs accomplish this by generating health state utilities (HSUs) via algorithms. Minimal important differences (MIDs) assist with the interpretation of HSUs by estimating minimum changes that are clinically significant. The overall goal of the proposed systematic review and meta-analysis is the development of comprehensive guidelines for MID estimation.Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 42 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…2 An alternative approach that could provide more meaningful insights is transforming various scales into a common instrument score. This method, coupled with modeling the risk difference for reaching the minimally important difference, 3 can better convey if the observed effects are clinically significant. Such an approach would enhance the utility of the findings for both clinicians and patients.…”
Section: Enhancing the Interpretation Of Continuous Outcomes And Subg...mentioning
confidence: 99%
See 4 more Smart Citations
“…2 An alternative approach that could provide more meaningful insights is transforming various scales into a common instrument score. This method, coupled with modeling the risk difference for reaching the minimally important difference, 3 can better convey if the observed effects are clinically significant. Such an approach would enhance the utility of the findings for both clinicians and patients.…”
Section: Enhancing the Interpretation Of Continuous Outcomes And Subg...mentioning
confidence: 99%
“…First, none of the 23 randomized clinical trials included in our review reported MIDs, and the outcomes measured by multiple scales across these trials were not reported consistently enough to calculate MIDs to achieve appropriate homogeneity. Second, there are no guidelines for MID estimation of generalized multiattribute utility instruments that were included in our study, 3 and determining MIDs sourced from previous work or establishing MIDs by consensus may introduce bias due to methodological subjectivity. 4 Moreover, the Cummings treatment effect model 5 indicates that MID will not appear in the early stage of the treatment; the difference in effect compared with the control group gradually increases as time progresses and, theoretically, it is expected to achieve and exceed MID.…”
Section: Enhancing the Interpretation Of Continuous Outcomes And Subg...mentioning
confidence: 99%
See 3 more Smart Citations